Enhancing Organizational Effectiveness: The Interplay of Human Resource Information Systems, Organizational Citizenship Behavior, and Organizational Communication: Meningkatkan Efektivitas Organisasi: Interaksi Sistem Informasi Sumber Daya Manusia, Perilaku Kewarganegaraan Organisasi, dan Komunikasi Organisasi - Mochamad Rizal Yulianto; Faizatul Humroh; Lilik Indayani; Alshaf Pebrianggara; Bunga Aulia Widyasmara (Universitas Muhammadiyah Sidoarjo, 2023)
This quantitative research investigates the dynamics of the human resource information system (HRIS), organizational citizenship behavior (OCB), and organizational communication in bolstering organizational effectiveness. A sample of 100 employees served as the basis of the study, and analytical tools such as classical assumption tests, multiple linear regression, F-test, T-test, and determinant coefficients were employed with the help of SPSS software. Primary data, garnered from questionnaires utilizing a Likert scale, ensured validity and reliability. The results manifested that HRIS and organizational communication substantially contributed to organizational effectiveness, while OCB had a less significant effect. Furthermore, the study illuminated a combined effect of HRIS, OCB, and organizational communication on organizational effectiveness. Among the variables, organizational communication was identified as the most significant factor. The study highlights the potential of effectively managed communication, alongside HRIS and OCB, to optimize organizational effectiveness. The implications thus emphasize the need for enhanced organizational communication practices, OCB, and HRIS implementation for improved organizational performance. Highlights: Organizational communication emerged as the most significant contributor to organizational effectiveness, underscoring the importance of effective internal communication practices. The Human Resource Information System (HRIS), despite its significant influence, indicates the need for technological enhancement in managing human resources for improved organizational performance. The study highlighted the potential of Organizational Citizenship Behavior (OCB) in boosting organizational effectiveness, even though its impact was less significant compared to other variables. Keywords: Human Resource Information Systems, Organizational Citizenship Behavior, Organizational Communication, Organizational Effectiveness, Quantitative Research.